How Best to Play the Role of Tumor Deposits in Stage III Colon Cancer? - Liu, Yunxiao; Zhang, Hao; Wang, Yuliuming; Wang, Chunlin; Xiong, Huan; Wang, Yang; Jing, Haoyu; Jiang, Xia; Hu, Hanqing; Tang, Qingchao; Wang, Guiyu (Frontiers in Oncology, 2022)
Background: The purpose of this study is to comprehensively evaluate the prognostic role of tumor deposits (TD) in stage III colon cancer. Methods: 24600 CC patients with III stage were collected from the Surveillance, Epidemiology, and End Result (SEER) database and 618 CC patients from the Second Affiliated Hospital of Harbin Medical University. All patients were divided into development, internal and external validation cohorts. The combination of positive lymph nodes (PLN) and the status or number of TD were defined as modified pN (mpN) and novel pN (npN). Cox proportional hazard regression model was used to analyze the relationship between CSS and mpN or npN. Cancer-specific survival (CSS) stratified by pN, mpN and npN was analyzed by the Kaplan-Meier curves. The area under the receiver operating characteristic curves (AUC) were used to demonstrate the predictive abilities of pN, mpN and npN stage. The validation cohorts were used to validate the results. Results: Cox proportional hazard regression model showed that mpN and npN were an independent prognostic factor for CSS. AUC showed that the predictive accuracy of mpN was better than that of pN stage for 5-year CSS in the development (0.621 vs 0.609, P < 0.001) and internal validation cohort (0.618 vs 0.612, P = 0.016) and the npN was also better than the pN stage for 5-year CSS in the development (0.623 vs 0.609, P < 0.001) and internal validation cohort (0.620 vs 0.612, P = 0.001). However, there was no significant difference between the AUCs of mpN and npN. And the pN stage for 5-year CSS in external validation cohort is 0.606vs 0.563, P = 0.045. Conclusions: In stage III CC, mpN and npN may be superior to pN stage in assessing prognosis, suggesting that the TD information should be included in pN stage.